Custos de produção e rentabilidade na produção de soja na propriedade rural da família ABC, safra 2021/2022 - Willig, Leonardo Augusto (2022)
The growing demand for food makes agriculture one of the most important and economically stable sectors in the world, which lack comprehensive planning and decision-making in accordance with the producer's investment, and the environment in which the cultures are inserted, which can be obtained with accounting assistance. Therefore, the present study aimed to analyze the production costs and profitability in the production of 2021/2022 soybean crop, in a small rural property with family labor, located in the municipality of Lagoa dos Três Cantos. The study was carried out based on a quantitative research, where the owner's data was analyzed through notes and invoices, bringing in the present work accounting and agronomic references on the cultivation of soybeans and the cultivation operations that the producer carried out. . In addition, all the costs incurred in growing soybeans are included, from planting to harvesting, as well as the profitability obtained. With the analysis, the result was that the total costs of growing soybeans in the 2021/2022 season were R$ 84,591.85, but on the other hand, the producer still made a profit of R$ 63,456.35.